MEASUREMENT AND INFRASTRUCTURE MANAGEMENT IN MADRASAH ALIYAH PRIVATE AL-WASHLIYAH KESUNG MESJID - Mesiono Mesiono; Ria Sartika; Rudi Hasibuan (Jurnal Sabilarrasyad, 2020)
Facilities and infrastructure management are facilities and infrastructure management activities carried out by schools to support all activities, both learning activities and other activities so that all activities run smoothly. Intending to use and maintain facilities and infrastructure effectively and efficiently and always in a ready-made condition when needed by all school personnel This research aims to describe the results of research regarding: (1) planning of facilities and infrastructure; (2) procurement of facilities and infrastructure; (3) maintenance of educational facilities and infrastructure in MAS Al-Washliyah Kp. The mosque is a descriptive study with a qualitative approach research method. The subjects of this study were the Head of Madrasah, Waka Sarpras, and Staf TU